Alleviation of morphophysiological dormancy in seeds of the Australian arid-zone endemic shrub, Hibbertia glaberrima F. Muell. (Dilleniaceae) - Dalziell, Emma; Erickson, T.; Hidayati, S.; Walck, J.; Merritt, D. (CABI Publishing, 2018)
© Cambridge University Press 2018. Morphophysiological dormancy (MPD) is predominantly found in seeds of temperate regions and is uncommon in arid biomes. MPD has been reported in a number of Hibbertia (Dilleniaceae) species of temperate Australia, and in a single species of the arid zone, H. glaberrima. This study aimed to examine the dormancy and germination ecology of seeds of H. glaberrima. Seeds were subjected to temperature stratification treatments designed to mimic summer and autumn conditions in the Pilbara region of Western Australia. Seed germination and embryo growth were measured. We also tested the interaction between temperature stratification and cycles of drying and wetting designed to mimic sporadic rainfall events. All temperature and moisture treatments were tested in combination (+/-) with the smoke-derived chemical karrikinolide (KAR1). Exposing dormant seeds to temperatures suitable for warm stratification (35°C) for = 8 weeks, followed by incubation at 25°C, resulted in significantly higher germination compared with non-stratified seeds. Exposing seeds to dry/wet cycling in conjunction with temperature stratification did not significantly increase germination. Exposure to KAR1 increased germination under most conditions. Once seeds are shed during October to December, they are exposed to hot and sporadically wet conditions over summer, allowing MPD to be overcome in a proportion of the seed population. Seeds may germinate in autumn (March to April), in conjunction with cooler temperatures. More deeply dormant individuals may require more than one summer to overcome dormancy. Similar to other species occurring in fire-prone ecosystems, fire also plays a crucial role in the germination ecology of H. glaberrima.